Recording of bruxism events in sleeping humans at home with a smart instrumented splint. Issue 1 (2nd January 2022) - Robin, Olivier; Claude, Arthur; Gehin, Claudine; Massot, Bertrand; McAdams, Eric
ABSTRACT: Objective : The aim of this paper is to report quantitative and qualitative characteristics of bruxism events recorded in sleeping humans with a new smart ambulatory system specifically designed to measure dental clenching and grinding forces. The device is wireless and rechargeable, which enables its use over extended periods. Methods : Thirty recordings were obtained from volunteer subjects who wore the device at home during 10 consecutive nights (Clinicaltrials.gov N° NCT03363204). Results : The recordings showed that the system was able to successfully monitor bruxism during 10 consecutive nights, allowing a quantitative (number, duration, intensity, distribution during the night), as well as a qualitative characterization of the bruxism events (clenching vs. grinding). Discussion : This system could offer new perspectives in the field of bruxism, either as a research tool for clinical studies or as a medical device for the ambulatory home-based monitoring of bruxism.